Estatura y salud nutricional en la Italia mussoliniana, 1922-1939 - Javier Puche; Pedro M. Pérez Castroviejo (Ler História, 2019)
This article analyses the nutritional status during the interwar period. It studies the fascist Italian period (1922-1940). As an indicator of the biological well-being of the populations, the height data of the military replacements constitutes the main source of study. The results reveal that, contrary to other European dictatorships, the health and nutrition conditions of Italian male populations improved during the Mussolini period. Although the real wages of the working classes decreased since the mid-twenties, the progress of health and epidemiological conditions -decline in the infant mortality and infectious diseases-, and the development of an incipient social state in basic factors such as health, education and pensions, contributed to improve the biological well-being of the Italian population as a whole, especially in the 1920´s.